MANAJEMEN JARINGAN DALAM PILKADA (Studi Kasus: Kerjasama antara Pasangan Calon Kepala Daerah âJunaedi âMukti Agung Wibowoâ dengan Kiai sebagai Strategi Kampanye dalam Pemenangannya pada Pilkada Kabupaten Pemalang Tahun 2010) - , ELDO ESFANDYARI, Dra. Ratnawati, SU ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Performance of Head of Districtâs Electoral in Pemalang regency in 2010 were won by \" H. Junaedi - Mukti Agung Wibowo \" the selection of the Regent and Vice Regent are interesting to study . Victory of the phenomenal couples utilizing charisma and clerical influence in increasing the mass to seize the seat of the Regent and Vice Regent . Research about the election of regent was conducted to detect the operation of the network management between candidate of the regent and vice- regent with clerics in mass mobilization. Network whose has role and activities according to the natural environment of clerics on Islamic domicile . Network Management theory is used to detect the political campaign strategy by applying the indicator. This research used qualitative methods with case studies . Data collection techniques was conducted by selected informant interviews with the method of ' snowball sampling ' and study documentation . Data analysis was conducted by reducing , presenting and making a conclusion of data obtained from the observation of key indicators based on Theory Management Network , like an activity identification of perception, potential , the rules arrangement and present the interaction tool . The results of research which conducted by the analysis of Network Management Theory is obtaining new knowledge , like a cooperation in the elections which managed by network management. Researchers found a unique major value which have a role in the election that is a bond of brotherhood . Bond of brotherhood was very supportive the cooperation between candidate pairs and clerics, which can be managed more easily by network management , especially in integrating perception , establish the rules of cooperation , and conduct surveillance field activities.